PERAN GURU SEBAGAI MOTIVATOR DALAM MENINGKATKAN KREATIVITAS SISWA PADA MATA PELAJARAN SOSIOLOGI DI SMA - Okta Suhendra; Sulistyarini Sulistyarini; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to give explaination the Role of Teachers as Motivators in Improving Student Creativity in Sociology Subjects in class XI IIS Muhammadiyah 2 Pontianak High School. This research aims to determine the teacher’s role as a motivator in improving student creativity and forms of creativity developed by teachers on sociology subjects. This research uses a qualitative approach with descriptive methods. The Data  collection techniques were observation, interviews and documentation while the data collection tools were observations guides, document and cameras. The informants in this study were sociology teachers and class XI students at IIS Muhammadiyah 2 Pontianak Senior High Shool. The result showed that, (1) The role of the teachers as a motivator in enhancing student creativity in sociology teachers and class XI IIS Muhammadiyah 2 Pontianak Senior High was well done by the teachers in the classroom, this was evidenced when starting learning the teachers opened by telling stories according to the materials learn, respond well when student argue and explain again if not understood, to arouse students learning enthusiasm teachers intersperse learning with games, encourage students to continue learning, try to achieve high achievements and boast parents, stressing learning is important for the future with provide motivation that encourages students to actively learn. (2) The forms of student creativity that are enhanced by the teahers as a motivator in the subjects of sociology learning are in terms of being active in discussions, asking questions, and expressing opinions during the teaching and learning process. Keywords: Teachers’s Role, Students’s Creativity